PENETAPAN KADAR FLAVONOID EKSTRAK DAUN ANDONG (Cordyline Fruticosa (L.) A. Cheval) BERDASARKAN VARIASI PELARUT EKSTRAKSI MENGGUNAKAN METODE SPEKTROFOTOMETRI ULTRA VIOLET -VISIBEL - Imas Maesaroh; Linda Alfiani; Wawang Anwarudin; Herliningsih Herliningsih (Jurnal Komunitas Farmasi Nasional, 2021)
Andong leaves (Cordyline fruticosa (L.) A. Cheval) contain secondary metabolites including saponins, tannins, flavonoids, steroids, polyphenols, polysaccharides, calcium oxalate, and iron. This study aims to determine the levels of flavonoids in andong leaf extract (Cordyline fruticosa (L.) A. Cheval) using 70% ethanol extraction solvent and 96% ethanol using Ultra Violet – Visible spectrophotometric method. The research method used in this research is experimental laboratory. The results of the qualitative test on both samples showed the presence of flavonoids contained in the leaves of Andong (Cordyline fruticosa (L.) A. Cheval). Absorbance measurements were carried out on the sample, carried out at a wavelength of 400 nm. The results of the quantitative test of flavonoid content in 70% ethanol solvent were 0.811% and flavonoid levels in 96% ethanol solvent were 0.769%.